Working In Romania For The Wellbeing For All: Implementing Pope Francis’ Vision Of A New Economy (The Macau Ricci Institute Journal, 2023)
For many years Ruth Zenkert cooperated with Georg Sporschill in various projects in Vienna and Eastern Europe to reach out to Roma children who have been excluded from society. In four short stories Zenkert describes her experiences in dealing with Roma children while Friedhelm Hengsbach, who is considered as one of the leading social ethicists in Germany, suggests a few key elements of the new vision of the economy of Pope Francis especially in his Encyclical Letters Evangelii gaudium (2013) and Laudato si’ (2015).